2001
DOI: 10.1016/s0896-6273(01)00422-6
|View full text |Cite|
|
Sign up to set email alerts
|

Polyglutamine-Expanded Ataxin-7 Antagonizes CRX Function and Induces Cone-Rod Dystrophy in a Mouse Model of SCA7

Abstract: Spinocerebellar ataxia type 7 (SCA7) is an autosomal dominant disorder caused by a CAG repeat expansion. To determine the mechanism of neurotoxicity, we produced transgenic mice and observed a cone-rod dystrophy. Nuclear inclusions were present, suggesting that the disease pathway involves the nucleus. When yeast two-hybrid assays indicated that cone-rod homeobox protein (CRX) interacts with ataxin-7, we performed further studies to assess this interaction. We found that ataxin-7 and CRX colocalize and coimmun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
216
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 244 publications
(226 citation statements)
references
References 45 publications
9
216
0
1
Order By: Relevance
“…However, SCA7 patients suffer from a cone-rod dystrophy. SCA7 knock-in mice and transgenic mice expressing polyQ-ataxin-7 controlled by prion promoter recapitulate degeneration of both cone and rod photoreceptors (La Spada et al, 2001;Yoo et al, 2003). In addition, cone function of R7E transgenic mice is impaired, although to a lesser extent than rod function, as revealed by ERGs (data not shown).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…However, SCA7 patients suffer from a cone-rod dystrophy. SCA7 knock-in mice and transgenic mice expressing polyQ-ataxin-7 controlled by prion promoter recapitulate degeneration of both cone and rod photoreceptors (La Spada et al, 2001;Yoo et al, 2003). In addition, cone function of R7E transgenic mice is impaired, although to a lesser extent than rod function, as revealed by ERGs (data not shown).…”
Section: Discussionmentioning
confidence: 84%
“…This mouse model reproduced the primary features of SCA7 pathology, including progressive functional alteration, followed by rod degeneration. Other SCA7 models with retinopathy include the transgenic mice expressing polyQ-ataxin-7 using a prion protein promoter (La Spada et al, 2001) and the SCA7 knock-in mice (Yoo et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expansion of the poly-glutamine tract of ataxin-7 is associated with a dominant neurological disorder, spinocerebellar ataxia type 7 (SCA7), which features cone-rod dystrophy-like retinal degeneration similar to the pathology linked to CRX mutations. Animal model studies and in vitro functional analysis suggest that Crx is a STAGA-dependent transcription activator (La Spada et al, 2001;Chen et al, 2004;Palhan et al, 2005). A polyglutamine-expanded ataxin-7 disrupts Gcn5 HAT activity, resulting in hypoacetylation of histones on Crx target genes and transcription impairment in a SCA7 transgenic mouse model.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…In contrast, studies on the yeast STAGA homolog SAGA suggested that expression of mutant ataxin-7 disrupted SAGA assembly and decreased HAT activity (McMahon et al 2005;Palhan et al 2005). It was further suggested that a photoreceptorspecific disruption in gene expression was associated with changes in the function of the photoreceptorspecific transcription activator CRX (La Spada et al 2001). It was reported that in mice overexpressing mutant ataxin-7, mutant ataxin-7 interacted with CRX and induced its decrease, as well as a decrease in CRX-mediated gene expression.…”
Section: Sca 7: a Role In Cell-specific Chromatin Structurementioning
confidence: 99%